2016 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2016
DOI: 10.1109/icassp.2016.7472087
|View full text |Cite
|
Sign up to set email alerts
|

Object recognition in art drawings: Transfer of a neural network

Abstract: We consider the problem of recognizing objects in collections of art works, in view of automatically labeling, searching and organizing databases of art works. To avoid manually labelling objects, we introduce a framework for transferring a convolutional neural network (CNN), trained on available large collections of labelled natural images, to the context of drawings. We retrain both the top and the bottom layer of the network, responsible for the high-level classification output and the low-level features de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…In [11], it is shown that recycling CNNs directly for the task of recognising objects in paintings, without fine-tuning, yields surprisingly good results. Similar conclusions were also given in [55] for artistic drawings. In [33], a robust low rank parametrized CNN model is proposed to recognise common categories in an unseen domain (photo, painting, cartoon or sketch).…”
Section: Related Worksupporting
confidence: 84%
See 1 more Smart Citation
“…In [11], it is shown that recycling CNNs directly for the task of recognising objects in paintings, without fine-tuning, yields surprisingly good results. Similar conclusions were also given in [55] for artistic drawings. In [33], a robust low rank parametrized CNN model is proposed to recognise common categories in an unseen domain (photo, painting, cartoon or sketch).…”
Section: Related Worksupporting
confidence: 84%
“…Several recent works show that recycling analysis tools that have been developed for natural images (photographs) can yield surprisingly good results for analysing paintings or drawings. In particular, impressive classification results are obtained on painting databases by using convolutional neural networks (CNNs) designed for the classification of photographs [11,55]. These results occur in a general context were methods of transfer learning [15] (changing the task a model was trained for) and domain adaptation (changing the nature of the data a model was trained on) are increasingly applied.…”
Section: Introductionmentioning
confidence: 99%
“…Others focus on applying and generalizing visual correspondence and object detection methods to paintings using both classical [41,18,7,4], as well as deep [6,8,47,20] methods. Most closely related to us is work of Yin et al [49], which used the same Brueghel data [1], annotating it to train detectors for five object categories (carts, cows, windmills, rowboats and sailbaots).…”
Section: Computer Vision and Artmentioning
confidence: 99%
“…This approach is by far the most used one. For the domain of artistic images, it has been used for style classification (2,12,27), object recognition in drawings (30) or iconographic characters (13), people detection across a variety of artworks (28), visual link retrieval (21), author classification (15,20) or several of those tasks at the same time (1).…”
Section: Deep Transfer Learning For Art Classification Problemsmentioning
confidence: 99%
“…7). Note that in (30), it has been shown that the low-level layer filters have been modified by a fine-tuning on an almost monochrome drawing training dataset. This suggests that the statistics of painting images are closer to those of natural images than those of drawing ones.…”
Section: Appendix a Experiments Setupmentioning
confidence: 99%